Do acne treatments affect insulin‐like growth factor‐1 serum levels? A clinical and laboratory study on patients with acne vulgaris. Issue 3 (19th May 2020) - Rodighiero, Eleonora; Bertolani, Mariabeatrice; Saleri, Roberta; Pedrazzi, Giuseppe; Lotti, Torello; Feliciani, Claudio; Satolli, Francesca
Abstract: Acne is a chronic inflammatory disease affecting sebaceous gland follicles. Lately, acne has considered an insulin‐like growth factor‐1 (IGF‐1) mediated disease. Recent research demonstrated that IGF‐1 levels decrease after 3 months of isotretinoin. The purpose of our study is evaluating the influence of acne treatments on IGF‐1 serum levels. Forty‐six subjects with acne vulgaris aged 14 to 30 years were subdivided into three groups according to their severity of acne and treated following the European Dermatology Forum guidelines. IGF‐1 was measured in patients before and after the treatment and then compared to the IGF‐1 of a healthy population of the same age. IGF‐1 resulted higher in patients than in controls but there was not a statistically significant variation after treatment. To the best of our knowledge, this is the first study evaluating the influence of topical and systemic acne treatment on IGF‐1 serum levels. In contrast with the literature, our results suggest that common therapies for acne are not able to significantly modify IGF‐1 serum levels.